Increasing child pedestrian and cyclist visibility: cluster randomised controlled trial. Issue 4 (13th March 2006) - Mulvaney, C A; Kendrick, D; Watson, M C; Coupland, C A C
Abstract : Study objective: Visibility aids have the potential to reduce child pedestrian and cyclist injury but scarce data exist relating to their use or to interventions for increasing visibility aid use among children. This cluster randomised controlled trial was designed to assess the use of free visibility aids one and eight weeks after their provision among primary school children in Nottingham, UK. Design: One class from each of 20 schools representing 377 children aged 7, 8, and 9 years old participated in the trial and were randomly assigned to treatment and control arms. Children in the intervention arm received two visibility aids, namely, a reflective and fluorescent slap wrap (an item that can be worn around an arm or trouser leg and is readily removed), and a reflective durable sticker in addition to educational material on the importance of being seen in the dark. Observers visited schools to observe use of reflective and fluorescent slap wraps, stickers, piping and patches on coats, and bags at baseline and at one and eight weeks after distribution of the visibility aids. The study used random effects logistic regression to calculate odds ratios (OR) and confidence intervals (CI). Main result: The results showed that children provided with free visibility aids were significantly more likely to use any visibility aid at one week (adjusted OR 59.5, 95% CI 18.5 to 191.0) and eight weeks (adjusted OR 5.9, 95% CI 3.4 to 10.4) after distribution than children in the control arm. Conclusions: Providing free visibility aids and an educational booklet on road safety significantly increases use of visibility aids for up to eight weeks during the winter among primary school children. On the basis of an eight week follow up trial in Nottingham of 20 classes of children aged 7 to 9 years old, these results suggest that campaigns providing free visibility aids to primary school children should be encouraged.